2014
DOI: 10.1007/978-3-642-54646-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Microporous Organic Polymers for Carbon Dioxide Capture

Abstract: Microporous organic polymers (MOPs) are a unique class of porous materials consisting solely of the light elements (C, H, O, N, etc.). A series of vivid characteristics of MOPs, such as high-specific surface area, good physicochemical stability, diverse pore dimensions, topologies, and chemical functionalities, make them suitable adsorbents for CO 2 capture. In this chapter, MOPs are categorized into four classes according to the types of organic reactions and the chemical structures of the resulting materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 177 publications
(208 reference statements)
0
5
0
Order By: Relevance
“…Conversely, PIMs are porous materials with free volumes derived from space-inefficient packing of highly rigid and contorted polymer chains (see section ). , Linear PIMs, such as PIM-1 and -7, are soluble in common organic solvents, and thus processable into defect-free membranes for CO 2 /CH 4 separation. However, other classes of MOPs lack solvent processability, and so they are generally used as fillers instead. Among the many MOPs, covalent-organic frameworks (COFs) are the only subclass that exhibit a structure of high crystallinity.…”
Section: Filler Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, PIMs are porous materials with free volumes derived from space-inefficient packing of highly rigid and contorted polymer chains (see section ). , Linear PIMs, such as PIM-1 and -7, are soluble in common organic solvents, and thus processable into defect-free membranes for CO 2 /CH 4 separation. However, other classes of MOPs lack solvent processability, and so they are generally used as fillers instead. Among the many MOPs, covalent-organic frameworks (COFs) are the only subclass that exhibit a structure of high crystallinity.…”
Section: Filler Materialsmentioning
confidence: 99%
“…COFs, on the other hand, are synthesized by several reversible organic reactions, such as the formation of B–O (boronate and boroxine), , CN (imine and hydrazone), , and C–N (triazine and imidization) , bond linkages, to create the necessary building blocks. As covalent bonds are formed, MOPs, as compared to inorganic porous materials (e.g., zeolites and CMSs) and MOFs, possess the advantages of persistent microporosity, strong physicochemical versatility, as well as robust structural and chemical stability, making them highly promising for CO 2 capture and CO 2 /CH 4 separation. , …”
Section: Filler Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon dioxide (CO 2 ) is one of the major greenhouse gases, which has been in focus in the recent years. CO 2 is responsible for 63% of the warming attributable to all greenhouse gases . Large amounts of the world's energy requirements are supplied by fossil fuels and the combustion of fossil fuels is one of the most dominant sources of carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays microporous organic polymers (MOPs) are considered to be pioneer materials due to their potential application in CO 2 capture and separation. [1][2][3] In comparison to inorganic porous materials (zeolites and activated carbons), inorganicorganic hybrids (metal-organic frameworks (MOFs) and zeolitic imidazole frameworks (ZIFs)), the major advantage of MOPs is that they combine high surface areas with good physicochemical stability and synthetic diversication. 4 Theoretical calculations as well as experimental results showed that porous materials containing nitrogen in the backbone exhibit enhanced CO 2 uptake and/or selectivity.…”
Section: Introductionmentioning
confidence: 99%